Deep-sea benthic habitats and the impacts of trawling on them in the offshore Greenland halibut fishery, Davis Strait, west Greenland. (8th September 2021) - Long, Stephen; Blicher, Martin E; Hammeken Arboe, Nanette; Fuhrmann, Mona; Darling, Michael; Kemp, Kirsty M; Nygaard, Rasmus; Zinglersen, Karl; Yesson, Chris
Abstract: The offshore Greenland halibut ( Reinhardtius hippoglossoides ) fishery, west Greenland, employs demersal trawl gear at depths of 800–1400 m. In contrast to many deep-sea fisheries, the target stock appears stable and the fishery is of significant economic importance. Recent Marine Stewardship Council certification of this fishery highlighted the paucity of knowledge of benthic habitats and trawling impacts, which this study aimed to address using a towed benthic video sled. The spatially discrete northern and southern areas of the fishery were found to be distinct in terms of the communities present, which non-metric multidimensional scaling suggests is primarily driven by temperature. Extensive physical evidence of trawling was observed. Trawling effort was significantly linked with community composition, with a negative association between trawling effort and abundance of some taxa, including some vulnerable marine ecosystem (VME) indicator species. Three potential VMEs are identified: (i) Flabellum alabastrum cup coral meadows; (ii) a Halipteris finmarchica sea pen field; and (iii) areas exhibiting mixed assemblages of VME indicators. Of immediate conservation concern is a H. finmarchica field, which seems to be at least regionally rare, is situated within the fringes of existing trawling effort and is currently afforded no protection by management measures.